An analysis of correctional education programs in Turkish prisons: perceptions of correctional educators and inmates - Ergin, Hakan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2012., 2012)
This study aims to explore the perceptions of correctional educators and inmates about the correctional education programs in a men’s and a women’s prison in Turkey and compare these perceptions of correctional educators and inmates to each other. Two groups, namely, correctional educators and inmates, participated in the study. Ten correctional educators, five from each prison, formed the first group of the participants in the study. Twenty inmates, ten from each prison, formed the second group. The data were collected through interview, a data collection technique of the qualitative method. A semi-structured interview form was developed. Both groups’ interviews included fourteen questions and the data gathered from the interviews were analyzed by the content analysis method. The findings of the study revealed that correctional educators are not as satisfied with taking place in correctional education environment as inmates are. However, it was further revealed that both correctional educators and inmates have similar perspectives about the factors that facilitate or complicate inmates’ success in correctional education programs, the necessity that all inmates should be provided with professional skills during their incarceration, the existence of the in-prison and after-prison positive effects of the correctional education programs on inmates and the existence of the problems in correctional education environments and the ways of solving these problems as well. In the light of the findings, recommendations for correctional educators, authorities and the entire society were made for the sake of improving the correctional facilities in Turkish prisons.
Keywords: Prisons -- Turkey.; Prisoners -- Education.; Correctional personnel.